Pengaruh Efikasi Diri dan Kemandirian terhadap Pilihan Karier Siswa - Wahyuningrum, Sri Rizqi; Fransiska, Milinda (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
One of the factors that needed to have the right career choice is self-efficacy. Self-efficacy is an individual’s bekief in his ability that influences the way individual reacts to certain situations ang conditions. The purpose of this study is to determine the relationship between self-efficacy and independence in student’s career choices and to find how big relationship between self-efficacy and independence in student’s career choice. The study uses quantitative methods. The data collection technique used is a questionnaire by distributing questionnaires to students. The population in this study was 345 while the sample was 70 students. The data analysis technique used is descriptive statistics, and for data analysis using simple linear regression, t test, and coefficient determination (R2). The results of the partial test (t test) for the self-efficacy variable obtained a significance value of 0,015 0,05 and a t-cont value of t-table where the t-count is 2,484 while the t-table is 1,977, meaning that there is significant relationship between self-efficacy and independence in career choice. From the results of the normality test, it knows that self-efficacy is normal with a significant value of 0,45452 0,05, which means that there is a relationship between self-efficacy and independence for the student’s career choice.